Preparation of conjugates based on colloidal gold nanoparticles for application in rapid detection of antibodies to hepatitis E virus - Galina I. Alatortseva; Lyubov N. Nesterenko; Irina I. Amiantova; Lyudmila N. Pritvorova; Vera V. Dotsenko; Vitaly V. Zverev; Oksana A. Svitich (Журнал микробиологии, эпидемиологии и иммунобиологии)
Relevance. Hepatitis E virus (HEV) is a common cause of viral hepatitis not only in areas with low levels of water supply and hygiene, but also in industrialized countries. Rapid tests development for the infection seromarkers detection in the absence of special equipment and trained staff remains the most important problem in improving the diagnosis of hepatitis E.